2017
DOI: 10.1007/s00436-017-5375-4
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism and inflammation in ear skin and in genital tissues of symptomatic and asymptomatic male dogs with visceral leishmaniasis

Abstract: Canine visceral leishmaniasis (CVL) is transmitted through vector, although venereal transmission has been suggested. This study aimed to compare the parasitic loads and inflammatory processes in genital tissues with ear skin from seropositive male dogs. Forty-five seropositive dogs were separated into groups containing symptomatic (n = 23) and asymptomatic (n = 22) animals. The control group (n = 2) healthy animals with seronegative and negative results in direct parasitological test. Samples of ear tip skin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
6
7
0
Order By: Relevance
“…These results suggest that the intensity of inflammation in the genital tract of dogs is associated with L . infantum load, in agreement with other authors [ 2 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results suggest that the intensity of inflammation in the genital tract of dogs is associated with L . infantum load, in agreement with other authors [ 2 , 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…After infection, the parasite can spread through the blood or lymphatic system to other organs of the genital tract. The high frequencies of positive results in vulvar skin observed in this study and in vulvar skin and prepuce reported in other studies [ 2 , 11 , 13 , 15 ] support that this route of infection of the genital tract may occur. However, future experimental studies on the kinetics of genital tract infection with L .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations